2011
DOI: 10.1111/j.1600-0722.2010.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dentin etching and chlorhexidine application on metalloproteinase‐mediated collagen degradation

Abstract: Dentin matrix metalloproteinases (MMPs) are involved in collagen degradation of resin-dentin interfaces. This study evaluated if collagen degradation can be prevented by chlorhexidine after different dentin demineralization procedures. Human dentin demineralization was performed with phosphoric acid (PA), EDTA, or acidic monomers (ClearfilSEBond and XENOV). Specimens were stored (24 h, 1 wk or 3 wk) in the presence or absence of chlorhexidine. In half of the groups, active MMP-2 was incorporated into the stori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
0
20

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(176 citation statements)
references
References 44 publications
5
151
0
20
Order By: Relevance
“…DIscussIOn Osorio et al (2011) were the first to demonstrate that MMP-2 has telopeptidase activity in dentin, although they did not use that term. Using an ICTP-specific ELISA assay, they incubated completely demineralized dentin beams in a medium for 1, 7, or 21 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…DIscussIOn Osorio et al (2011) were the first to demonstrate that MMP-2 has telopeptidase activity in dentin, although they did not use that term. Using an ICTP-specific ELISA assay, they incubated completely demineralized dentin beams in a medium for 1, 7, or 21 days.…”
Section: Resultsmentioning
confidence: 99%
“…#HU9655). The only source of ICTP telopeptide fragments in mineralized matrices is attributed to the telopeptidase activity of MMPs (Garnero et al, 1998(Garnero et al, , 2003Osorio et al, 2011). We determined matrix degradation by cysteine cathepsins by measuring the amount of solubilized C-terminal peptide, CTX, in the incubation medium using the Serum CrossLaps ELISA (Immunodiagnostic System, Scottsdale, AZ, USA).…”
Section: Solubilized Telopeptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…MMPs can be activated by the simple step of conditioning dentin with phosphoric acid (De Munck et al, 2009). Thus, the use of etch-and-rinse adhesive systems might produce a higher activation of endogenous MMPs in dentin, while in self-etching adhesive systems it is less pronounced (De Munck et al, 2009;Osorio et al, 2011), which can be translated in decreased interface degradation. In our study, this fact was not observed, since the etch-andrinse adhesive system did not show a higher degradation compared to the self-etch adhesive system.…”
Section: Discussionmentioning
confidence: 99%